(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
The aim of this study was to clinically evaluate the effectiveness of complete dentures fabricated by an advanced digital workflow using heat-cured acrylic resin and a Kravets verticulator, in comparison with dentures produced by a conventional technique based on cold-cured acrylic resin. Patients in the test and control clinical groups received complete dentures fabricated according to a CAD/CAM protocol with virtual design in Exocad, followed by three-dimensional assessment of dimensional accuracy between final dentures and their virtual prototypes. Clinical examinations included evaluation of temporomandibular joint (TMJ) function, masticatory muscles, denture retention and stability, as well as denture hygiene. Oral-health-related quality of life was assessed using the OHIP-14 questionnaire before treatment and during denture use. Throughout the 12-month follow-up, patients in both groups showed normal mouth opening without deviation or deflection and no clinical signs of TMJ disorders. In the test group, the mean occlusal discrepancy between final dentures and prototypes was minimal (approximately 30±4 µm in the maxilla and 29±4 µm in the mandible), whereas in the control group discrepancies exceeded 230 µm, which was associated with a higher frequency of discomfort complaints and the need for relining. Denture hygiene, assessed using the Jeganathan index, revealed a greater accumulation of deposits in the control group. Total OHIP-14 scores significantly decreased after treatment in both groups, but the clinical effect was more pronounced in the test group (∆OHIP-14 = 3.74 versus 2.65). These findings indicate high clinical effectiveness of the advanced digital technique for complete denture fabrication and its advantages in terms of prosthesis accuracy, retention, hygiene, and patient-reported quality of life.